Pengaruh Strategi Resource-Based terhadap Keunggulan Bersaing melalui Inovasi pada Usaha Mebel Kayu di Kota Pasuruhan - Darojatin, Kharisma; Surachman, Surachman; Andarwati, Andarwati (Jurnal Aplikasi Manajemen, 2016)
This study aimed to examine and determine the effect of resource-based strategy to innovation, the effect of resource-based strategies for competitive advantage, the effect of innovation on competitive advantage, and the effect of indirect resource-based strategy for competitive advantage through innovation in the wood furniture business in Pasuruan.This study is the explanation (explanatory research). The analysis tool is Structural Equation Modelling (SEM). Primary data were collected by field research methods. The data collection techniques is questionnaires and interviews. The sample in this study were 100 respondents wood furniture business in Pasuruhan. The results showed that the Resource-Based Strategy which is actualized in financial resources, physical resources, human resources, technological resources, and organization's reputation resources affect theinnovation that improved the innovation. The betterResource-Based strategy that can improve competitive advantage in terms of cost, quality, time, and flexibility. Improved the innovation in terms of process innovation, product innovation, organizational innovation, and business innovation can improve competitive advantage in the wooden furniture business in Pasuruan in terms of consumer recognition of the product, reduced costs, and improved product quality. Resource-based strategy has an indirect effect to competitive advantage through innovation on the wood furniture business in Pasuruan.